Manifestation of the Turkic worldview in the work «Irshad al-Muluukwa as-Salatiin»: Түркі дүниетанымы - Shalkarov, D.; Aubakirova, K. (Eurasian Journal of Religious Studies, 2021)
The article discusses the manifestations of the medieval Turkic worldview and culture, their direct impact on the Islamic world of the spiritual culture of that period and its viability. The Turkic Kipchaks, known in the historical arena as the Mamluks, came to power in the Islamic world, the Turkic language has a special place in society since that time, the language and its grammatical features were taught in the Islamic world. The distribution of a wide range is considered in detail. It is discussed not only the linguistic features of the Turks in the Kipchak language, but also the religious orientation of religious works written in Arabic and the ability to translate classical literature into the Turkic language. It is discussed that the work «Irshad al-Muluk wa as-Salatin», written in the 14th century, which contains most of the basic elements of the Kipchak language, was one of the most important works in the history of Turkic language and literature, the Turkic worldview. It is studied that this work was written in Kipchak by the order of Sultan Saifi Baiman in Alexandria, and hermeneutic and textual analysis of the texts is carried out. It is also considered to be one of the earliest written Kipchak inscriptions in Egypt. Key words: Turkic people, medieval Turkic worldview, Islamic culture, Mamluks, Turkic language.